Differences in the Level of Tiktok Addiction Between Males and Females Student in Secondary Education in Menganti Sub-District Gresik District - Findivia Egga Fahruni; Hadi Warsito Wiryosutomo; Maria Veronika Roesminingsih (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Tiktok is one of the most popular short video platforms today and many active users spend a lot of time watching Tiktok. This condition makes the phenomenon of Tiktok addiction widespread. So this article aims to investigate the level of Tiktok addiction based on male and female gender in junior high school students in Menganti Sub-District, Gresik District. This research approach is descriptive comparative. The population of this study includes all eighth grade students in Menganti, Gresik. While the sample is 344 grade VIII students in Menganti, Gresik, in detail there are 179 male students and 165 female students. The sample selection technique used random sampling at 4 schools, namely SMP Negeri 18 Gresik, SMP Negeri 29 Gresik, SMP NU Bahrul Ulum, and SMP Sunan Giri Menganti. Data collection techniques used closed questionnaires and documentation. The instrument used is a Tiktok Addiction Scale questionnaire and a matched list. The data were analyzed using the Mann Whitney non-parametric technique using SPSS. The findings of the study showed that there were differences in the level of addiction in male and female students in grade VIII in Menganti, Gresik. Tiktok addiction in male students is in the low category, while the level of Tiktok addiction for female students is in the medium category.